2010
DOI: 10.1158/1078-0432.ccr-10-0284
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Alterations and Allelic Imbalances Are Strong Prognostic Predictors in Osteosarcoma

Abstract: Purpose: Osteosarcoma, the most common primary malignant tumor of the bone, is characterized by complex karyotypes with numerous structural and numerical alterations. Despite attempts to establish molecular prognostic markers at the time of diagnosis, the most accepted predictive factor remains the histologic evaluation of necrosis after neoadjuvant chemotherapy. The present approach was carried out to search for genome-wide recurrent loss of heterozygosity and copy number variations that could have prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 47 publications
4
97
0
3
Order By: Relevance
“…29 Increased chromosomal instability has been associated with poorer outcome in osteosarcoma. 30 We took into account the possibility that copy number variability in the specimens we studied could be influencing our DNA methylation data, using parallel MspI profiling and showing that these assays did indeed appear to be capable of detecting these regions of copy number variation (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…29 Increased chromosomal instability has been associated with poorer outcome in osteosarcoma. 30 We took into account the possibility that copy number variability in the specimens we studied could be influencing our DNA methylation data, using parallel MspI profiling and showing that these assays did indeed appear to be capable of detecting these regions of copy number variation (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that matrigel, interacting with the microenvironment, might regulate tumor cell behavior providing the adequate cues for a gradual loss of stemness. Genetic alterations and cytopathological heterogeneity characterize osteosarcomas and contribute to the intractability of the disease [Smida et al, 2010]. Osteosarcoma has been proposed to be a differentiation-flawed disease [Siclari and Qin, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…O steosarcoma, the most common of primary bone malignancies, is among a group of mesenchymal cancers characterized by clinical, histologic and molecular heterogeneity, and karyotypes with a high degree of aneuploidy [Smida et al, 2010]. It is a highly aggressive tumor with a high metastasizing potential and, at present, it remains the second leading cause of cancer-related death for children and young adults [Ta et al, 2009].…”
mentioning
confidence: 99%
“…And there was a correlation between E-cadherin-regulated cell adhesion and anoikis evasion among human OS cells (MG-63) (Lin et al, 2014). At the same time, chromosomal abnormalities, such as amplifications of chromosomes 6p21, 8q24, and 12q14, as well as loss of heterozygosity of 10q21.1, 10 and 13, were identified as being among the most common genomic alterations in OS (Ta et al, 2009;Smida et al, 2010). Further more, the dysfunction of a variety of tumour associated genes, such as livin, had been proved to inhibit tumor cell apoptosis through multiple ways and be involved in OS pathogenesis (Li et al, 2014).…”
Section: Identification and Functional Analysis Of Differentially Expmentioning
confidence: 97%